A copper-based layered coordination polymer: synthesis, magnetic properties and electrochemical performance in supercapacitors. Issue 44 (21st October 2015) - Liu, Qi; Liu, Xiuxiu; Shi, Changdong; Zhang, Yanpeng; Feng, Xuejun; Cheng, Mei-Ling; Su, Seng; Gu, Jiande
Abstract : A layered copper-based coordination polymer ([Cu(hmt)(tfbdc)(H2 O)], Cu-LCP) has been synthesized, which shows ferromagnetic interactions between the adjacent copper(ii ) ions and an excellent capacitive performance in supercapacitors. Abstract : A copper-based layered coordination polymer ([Cu(hmt)(tfbdc)(H2 O)]; hmt = hexamethylenetetramine, tfbdc = 2, 3, 5, 6-tetrafluoroterephthalate; Cu-LCP) has been synthesized, and it has been structurally and magnetically characterized. The Cu-LCP shows ferromagnetic interactions between the adjacent copper(ii ) ions. Density functional theory calculations on the special model of Cu-LCP support the occurrence of ferromagnetic interactions. As an electrode material for supercapacitors, Cu-LCP exhibits a high specific capacitance of 1274 F g −1 at a current density of 1 A g −1 in 1 M LiOH electrolyte, and the capacitance retention is about 88% after 2000 cycles.